Service-learning in literacy education : possibilities for teaching and learning - Kinloch, Valerie, 1974-; Smagorinsky, Peter (Information Age Publishing, 2014)
This edited collection will stand as the first volume that specifically describes service-learning programs and courses designed as part of teacher education programs in the fields of literacy education, secondary English education, elementary language arts education, and related fields. The contributing authors describe the programs they have developed at their universities and/or in their local communities, providing information about the rationale for their initiative, the design of the course, the outcomes of the experience, and other matters that will help literacy educators develop similar courses and experiences of their own. Additionally, this edited collection will fill a great gap in the field's knowledge of alternative forms of teacher education. It will provide descriptions of service-learning initiatives that have been field-tested with demonstrable results. Thus far the field has produced widely scattered articles in journals covering a variety of disciplines, but no definitive collection of papers in which service-learning designed to promote literacy instruction is housed in a single volume edited for cross-referencing and thematic categorization. The two editors have developed courses and received grants to support service-learning initiatives at their universities and believe that others might develop similar programs if they had better understandings of their value and design. Their intention with this volume is to promote service-learning more broadly among literacy educators.